075 The Use of GRADE Methods in the World Health Organization (Who) Public Health Guidelines (PHG): Distribution of Strength of Recommendations and Confidence in Estimates of Effect. (15th August 2013) - Elias, P; Norris, S; Brito, J; Stoltzfus, R; Bero, L; Djulbegovic, B; Neumann, I; Montiori, V; Guyatt, G
Abstract : Background: A perception exists that expert guideline panellists are sometimes reluctant to offer weak/conditional/contingent recommendations. GRADE guidance warns against strong recommendations when confidence in estimates of effect is low or very low (low or very low quality evidence), suggesting that such recommendations may seldom be justified. Objectives: To characterise the distribution of strength of recommendations and confidence in estimates of effect in WHO guidelines that have used the GRADE approach and graded strength of recommendations and confidence in effect estimates. Methods: We reviewed guidelines listed in the WHO guidelines database as of November 2012. We identified those that use GRADE and, in these guidelines, examined the distributions of strong and weak and associated confidence in estimates of effect (high, moderate, low, and very low). Results: We identified 116 WHO guidelines; 48 (41.3%) referred to GRADE methods, and 43 (37%) utilised GRADE and provided both a strength of recommendation and confidence in estimates grading. These 43 guidelines included 456 recommendations, of which 290 (63.6%) were strong and 166 (36.4%) were conditional/weak. Of the 290 strong recommendations, 97 (33.4%) were based on evidence warranting low confidence in estimates of effect and 63 (21.7%) on evidence warranting only very low confidence. Discussion: Strong recommendations based on low or very low confidence in effect estimates are very frequently made in WHO guidelines. Further study to determine the reasons for such recommendations is warranted. Implications for Guideline Developers/Users: Guideline authors should provide a clear, compelling rationale for any strong recommendations based on low confidence estimates.